Assessment of the benefit of cervical cerclage in mothers diagnosed with short cervix - Pravallika, Bammidi Padma; Rao, Bhushan; Kakariya, Bhavna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Cervical incompetence is the inability of the uterus to retain a pregnancy in the absence of signs and symptoms of clinical contractions or labour or both in the second trimester of pregnancy. Cervical cerclages could be better management for pregnancy outcome. In the present study, we evaluated the pregnancy outcome in mothers diagnosed with short cervix who underwent cervical cerclage during second trimester in tertiary care institute. Methods: This research was conducted as prospective analytical study during the period of 25 months from January 2021 to April 2022. The cervical cerclage was performed as per McDonald’s technique under short anaesthesia among the mothers who presented with short cervix was posted for cervical cerclage operation as per the standard procedure. Results: In the present study, among 10 mothers with previous one second trimester miscarriage 7 cases (70.0%) reached full term, among 5 patients with previous two second trimester miscarriages 3 cases (60.0%) reached full term and among 2 patients with previous three second trimester miscarriages and 2 cases (100%) reached full term. Overall, 12 cases (70.58%) out of 17 patients with previous second trimester miscarriages had reached full term. Moreover, among 19 mothers with previous one preterm delivery 15 cases (78.94%) reached full term and among 8 mothers with previous two preterm deliveries and 5 cases (62.50%) reached full term. Overall, 20 cases (74.07%) of 27 mothers with previous preterm deliveries had reached full term. The majority of mothers (45, 97.82%) had live births. Only 1 case (2.17%) had second trimester miscarriage. Conclusions: this study observed the cervical cerclages an effective method in management of short cervix and cervical incompetence.